The coolest beard - Tekle, Betty (Albert Whitman & Company, 2023)
Isaac wants to grow a beard, just like his dad, who always seems to be the coolest person in the barbershop, but after trying for weeks with no success, he discovers there are other ways to imitate his father's coolness.